Pengaruh Kualitas Pelayanan dan Citra Merk Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Resto Pondok 21 Kota Metro - Rian Bagas Kara; Fitriani; Nina Lelawati (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the effect of service quality and brand image on consumer loyalty with consumer satisfaction as an intervening variable at Pondok 21 Resto, Metro City. This research is a type of research is quantitative research. The instruments used in this study were questionnaires and observations. The data analysis technique performed is using a path analysis tool. The results of the study show that service quality has a direct effect on consumer loyalty at Pondok 21 Resto, Metro City. Brand image has a direct effect on consumer loyalty at Pondok 21 Resto, Metro City. Service quality has a direct effect on customer satisfaction at Pondok 21 Resto, Metro City. Brand image has a direct effect on customer satisfaction at Pondok 21 Resto, Metro City. Consumer satisfaction has a direct effect on consumer loyalty at Pondok 21 Resto, Metro City.